2008
DOI: 10.1021/pr800550q
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Provides New Insights into the Fiber Elongating Process in Cotton

Abstract: A comparative proteomic analysis was performed to explore the mechanism of cell elongation in developing cotton fibers. The temporal changes of global proteomes at five representative development stages (5-25 days post-anthesis [dpa]) were examined using 2-D electrophoresis. Among approximately 1800 stained protein spots reproducibly detected on each gel, 235 spots were differentially expressed with significant dynamics in elongating fibers. Of these, 120 spots showed a more than 2-fold change in at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
106
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 71 publications
15
106
0
7
Order By: Relevance
“…In Arabidopsis, PA could function as a signal to activate the NADPH-oxidase and lead to the ROS production (Zhang et al, 2009). Consistent with the previous proteomic analysis, our results indicated that GaPLD1 was highly expressed in fibers at 20 DPA, H 2 O 2 level of which was at the peak (Potikha et al, 1999;Yang et al, 2008b), and suggested that GaPLD1 might participate in signal transduction for the release of ROS via activation of NADPH-oxidase in elongating fiber cells. The other fiber-related GaPLD gene, GaPLD2, might also be associated with ROS.…”
Section: Expression Profiles Of Gapld Genessupporting
confidence: 90%
See 2 more Smart Citations
“…In Arabidopsis, PA could function as a signal to activate the NADPH-oxidase and lead to the ROS production (Zhang et al, 2009). Consistent with the previous proteomic analysis, our results indicated that GaPLD1 was highly expressed in fibers at 20 DPA, H 2 O 2 level of which was at the peak (Potikha et al, 1999;Yang et al, 2008b), and suggested that GaPLD1 might participate in signal transduction for the release of ROS via activation of NADPH-oxidase in elongating fiber cells. The other fiber-related GaPLD gene, GaPLD2, might also be associated with ROS.…”
Section: Expression Profiles Of Gapld Genessupporting
confidence: 90%
“…In the previous proteomic studies, PLDs were proposed to be involved in cotton fiber development. The PLD proteins began to accumulate during the rapid fiber elongation, and reached up to a peak simultaneously with the initiation of second cell wall synthesis (Hu et al, 2013;Yang et al, 2008b). Moreover, consistent with the PLD protein expression profile, the PA content was low in the elongating fibers and high in the mature ones (Wanjie et al, 2005).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, even this group did not produce full-length cotton cDNAs to reconfirm the identified proteins, whereas all the currently identified proteins, except for ␣-1,4-glucan phosphorylase (spot 22), were confirmed by putative full-length cotton cDNAs (Table I). As shown in supplemental Table 4, no significant qualitative difference was observed when comparing the current proteome with that reported by Yang et al (40) and Zhao et al (39), who both used a modified protein extraction protocol (41). The Ligon lintless (Li 1 ) mutant and the fl mutant were used by Zhao et al (39) and in the current work, respectively, to elucidate fiber growth mechanisms.…”
Section: Specific Combinations Of Nucleotide Sugars Rescue Short Rootmentioning
confidence: 69%
“…Two previous cotton fiber proteomes (18,40) identified proteins by searching the database against known polypeptides or ESTs in all plant species or other organisms. Another group used a locally constructed 376,100 Gossypium EST database to search for cotton polypeptides (39).…”
Section: Specific Combinations Of Nucleotide Sugars Rescue Short Rootmentioning
confidence: 99%